Mass Occurrence of Hokkaidoconchid Gastropods in the Upper Jurassic Methane Seep Carbonate from Alexander Island, Antarctica - Kaim, Andrzej; Kelly, Simon R.A. (Antarctic Science, 2009)
The Tithonian (Upper Jurassic) methane seep carbonate of the Gateway Pass Limestone Bed (Alexander Island, Antarctica) yields enormous numbers of the minute gastropod mollusc, Hokkaidoconcha hignalli sp. nov. together with an unidentified limpet gastropod and occasional protobranch and lucinid bivalves. This assemblage constitutes one of the most abundant (by means of the specimen number) records of Jurassic chemosynthesis-based communities. The gastropod family Hokkaidoconchidae is extremely common in Cretaceous hydrocarbon seep carbonates from Japan and is known also from Upper Jurassic/Cretaceous hydrocarbon seep carbonates in California. It is an extinct family closely related to modern seep and vent dwelling Provannidae. This is the first confirmed record of this family in the Southern Hemisphere, indicating its surprisingly early and widespread distribution reaching high latitudes.